The impact of acquired coagulation factor XIII deficiency in traumatic bleeding and wound healing - Kleber, Christian; Sablotzki, Armin; Casu, Sebastian; Olivieri, Martin; Thoms, Kai-Martin; Horter, Johannes; Schmitt, Felix; Birschmann, Ingvild; Fries, Dietmar; Maegele, Marc; Schöchl, Herbert; Wilhelmi, Michaela (Critical care, 2022)
Factor XIII (FXIII) is a protein involved in blood clot stabilisation which also plays an important role in processes including trauma, wound healing, tissue repair, pregnancy, and even bone metabolism. Following surgery, low FXIII levels have been observed in patients with peri-operative blood loss and FXIII administration in those patients was associated with reduced blood transfusions. Furthermore, in patients with low FXIII levels, FXIII supplementation reduced the incidence of post-operative complications including disturbed wound healing. Increasing awareness of potentially low FXIII levels in specific patient populations could help identify patients with acquired FXIII deficiency; although opinions and protocols vary, a cut-off for FXIII activity of ~ 60-70% may be appropriate to diagnose acquired FXIII deficiency and guide supplementation. This narrative review discusses altered FXIII levels in trauma, surgery and wound healing, diagnostic approaches to detect FXIII deficiency and clinical guidance for the treatment of acquired FXIII deficiency.
Gesehen am 02.07.2022